MiSeq raw sequences (Run 1) of the V4 region 16S rRNA gene from the spleens of 355 murinae from Senegal and 21 positive and negative controls (part 2 to 4) - Galan, Maxime; Razzauti, Maria; Bard, Emilie; Bernard, Maria; Brouat, Carine; Charbonnel, Nathalie; Dehne-Garcia, Alexandre; Loiseau, Anne; Tatard, Caroline; Tamisier, Lucie; Vayssier-Taussat, Muriel; Vignes, Hélène; et al. (Dryad Digital Repository, 2016)
This ZIP file contains the FASTQ files of the paired-end reads (R1: reads 1; R2: reads 2) produced for each individual in duplicate or triplicate using the MiSeq platform (Run 1). The 823 multiplexed PCR products were indexed using both forward and reverse indices. The list of the 355 multiplexed samples and the 21 positive and negative controls are provided in the following XLSX file titled: Information concerning the samples multiplexed in the MiSeq Run 1 & 2.